2005
DOI: 10.1002/ccd.20353
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of patient radiation doses during transcatheter closure of ventricular and atrial septal defects with Amplatzer devices

Abstract: The purpose of this study was to estimate the radiation dose to which children are exposed during cardiac catheterizations for the treatment of ventricular and atrial septal defects. Radiation doses were estimated for 46 children aged 1-18 years. These children were treated for secundum atrial septal defects (ASD group) for perimembranous ventricular septal defects (VSD group) or underwent a routine diagnostic catheterization (diagnostic group). Thermoluminescent dosimeters (TLDs) were attached in locations, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Adult patient radiation doses have been evaluated in different types of cardiovascular interventions: simple diagnostic cardiac and peripheral catheterization [11], stent-grafting of abdominal aortic aneurysms [12], permanent cardiac pacemaker implantation procedures [13], during transcatheter closure of ventricular and atrial septal defects [14]. The advent of new imaging techniques such as the intracardiac echocardiography has the potential to improve safety and effectiveness of a large number of procedures reducing the amount of radiation for patients and operators.…”
Section: Discussionmentioning
confidence: 99%
“…Adult patient radiation doses have been evaluated in different types of cardiovascular interventions: simple diagnostic cardiac and peripheral catheterization [11], stent-grafting of abdominal aortic aneurysms [12], permanent cardiac pacemaker implantation procedures [13], during transcatheter closure of ventricular and atrial septal defects [14]. The advent of new imaging techniques such as the intracardiac echocardiography has the potential to improve safety and effectiveness of a large number of procedures reducing the amount of radiation for patients and operators.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the long-term risks of fatal malignancy following a single pediatric catheter investigation seems very low, the effect of repetitive exposure is unclear [7], [31]. In general, DAP values measured during pediatric catheterizations show an excellent correlation with the entrance radiation dose and skin doses measured with thermoluminescent dosemeters (TLDs) or can be transferred by calculation models to effective doses and are therefore valid to obtain a real-time measurement of the total amount of radiation used [4], [13], [32], [33], [34], [35]. Similar results are obtained when calculating effective doses from DAP as published by the International Commission on Radiology Protection and measuring the effects on DNA damage [8].…”
Section: Discussionmentioning
confidence: 99%
“…The mean body weight was 28.7 kg (median 21,0) and the mean fluoro-time 22.3 min (median 16.5 min) [4]. They reported mean DAP doses of 1.071 cGy·cm 2 (median 873 cGy·cm 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A compelling review of image-guided surgical applications can be found in (Peters, 2006). There are two alternatives for minimally invasive ASD closure procedures: one using a catheter-based closure, usually under contrast-enhanced fluoroscopy (Faella et al, 2003;Papadopoulou et al, 2005); and another using rigid instruments through the chest wall (Suematsu et al, 2004), demonstrated in animals. Although clinically available, the catheter-based procedure has major disadvantages: it can only be used on a fraction of ASD (Patel et al, 2006), it excludes procedures on small children (Paragios., 2003), and it is generally performed under a high Xray dose (Papademetris et al, 2003).…”
Section: Introductionmentioning
confidence: 99%